Pengaruh Kepuasan Kerja dan Pengawasan Terhadap Disiplin Kerja Karyawan Akademi Kebidanan Internasional Pekanbaru - Iskandar Iskandar (Akuntansi & Ekonomika, 2018)
This research was conducted at the Pekanbaru International Midwifery Academy. The purpose of this study was to determine the effect of simultaneous and partial satisfaction and supervision on employee work discipline at the Pekanbaru International Midwifery Academy. To achieve these objectives, research was conducted using a sample of 35 people, using the Census method. Data analysis method uses simultaneous tests and partial tests. The results of this study produce the influence of satisfaction and supervision on employee work discipline at the Pekanbaru International Midwifery Academy contributing a large influence on employee work discipline. Simultaneously and partially the test results are influential. Recommendations that can be submitted by the author are agencies to further enhance satisfaction and supervision because this variable greatly influences employee work discipline which of course has an impact on the performance of the employees themselves in carrying out their activities.